2022
DOI: 10.1038/s41409-022-01781-9
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of HLA-mismatched unrelated donor transplantation with post-transplant cyclophosphamide versus HLA-haploidentical transplantation in patients with active acute myeloid leukemia

Abstract: HLA-haploidentical allogeneic hematopoietic stem cell transplantation (Haplo-HCT) is frequently used as treatment for patients with active acute myeloid leukemia (AML). Here, we investigated whether 9/10 HLA-mismatched unrelated donor transplantation (MMUD-HCT) with post-transplant cyclophosphamide (PTCy) is an adequate alternative. Inclusion criteria in this retrospective registry study consisted of adult patients, first HCT with a Haplo donor or MMUD between 2010 and 2020 using PTCy as graftversus-host disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…This approach allows us to find a donor for virtually all patients, and, because of greater HLA disparities, a greater graft-versus-leukaemia effect can be assumed, also in the setting of RR AML. Baron et al [41] reported that there was a trend towards better OS with mis-matched unrelated donors (mMUD) than with Haplo treatment. In this registry study, GVHD prophylaxis was administered uniformly via the PTCY platform.…”
Section: Results From Retrospective Studiesmentioning
confidence: 99%
“…This approach allows us to find a donor for virtually all patients, and, because of greater HLA disparities, a greater graft-versus-leukaemia effect can be assumed, also in the setting of RR AML. Baron et al [41] reported that there was a trend towards better OS with mis-matched unrelated donors (mMUD) than with Haplo treatment. In this registry study, GVHD prophylaxis was administered uniformly via the PTCY platform.…”
Section: Results From Retrospective Studiesmentioning
confidence: 99%
“…The unfavourable outcome of r/r AML patients transplanted from HLA‐mismatched donors highlights the need for novel approaches, such as replacing antibody‐based in vivo T‐cell depletion with “post‐transplant cyclophosphamide.” A recently published retrospective study showed a promising survival improvement in patients transplanted from HLA‐mismatched unrelated donors when cyclophosphamide was used for post‐transplant immunosuppression in AML patients with active disease 40 …”
Section: Discussionmentioning
confidence: 99%
“…A recently published retrospective study showed a promising survival improvement in patients transplanted from HLA-mismatched unrelated donors when cyclophosphamide was used for post-transplant immunosuppression in AML patients with active disease. 40 Interestingly, even patients with signs of impending relapse showed promising survival at 2 years, reinforcing the importance of close monitoring and early interventions such as accelerated immunosuppression tapering, pre-emptive donor lymphocyte infusions and targeted therapies in the setting of impending relapse after alloSCT. [41][42][43] Of note, as with other retrospective analyses, the analysis of treatment and transplant outcomes may be confounded by a selection bias in the choice of conditioning therapies.…”
Section: F I G U R Ementioning
confidence: 99%
“…Given the rapid advances in HLA typing and the major improvements in GvHD prophylaxis, as observed with high-dose post-transplant cyclophosphamide [ 70 , 71 ], for example, the current indications will probably evolve in the next future, driven by the impressive amount of HLA data provided by NGS and the constant increase of allo-HSCTs from unrelated and HLA-mismatched donors. The experience acquired with high-dose post-transplant cyclophosphamide for haploidentical transplants has prompted transplant physicians to enhance its administration in the HLA-mismatched unrelated setting in recent years [ 72 , 73 ], under the hypothesis that such GvHD prophylaxis would be superior to the “conventional” one based on calcineurin inhibitors, in the presence of one or more HLA incompatibilities. Similarly, considerations about the intensity of the conditioning regimen are warranted, since the expected organ toxicity is tightly linked to the risk of acute GvHD, acting as a potential trigger, enhanced by HLA incompatibilities.…”
Section: Translation Into Daily Practicementioning
confidence: 99%